POTRET KONDISI JURNAL ILMIAH BERBASIS OPEN JOURNAL SYSTEM DI LINGKUNGAN LEMBAGA PELATIHAN BALITBANG DIKLAT KEMENTERIAN AGAMA - Dedi Restendi; Ayi Nasrudin (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2022)
Abstract There was a migration in periodic journals publishing from printed journals to the Open Journal System (OJS) at training institutions under the auspices of Badan Litbang dan Diklat Kementerian Agama in 2020. This study aims to determine the current condition of OJS in terms of accessibility, consistency, accreditation, and the number of articles published in year 2019 and 2020. Data collection was carried out through document review conducted by accessing and checking 17 OJS address sites for training institutions under the Ministry of Research and Development Agency. Religion. The results of the study explain that all training institutions have open scientific journal website addresses, 2 journals cannot be accessed, 15 journals have not been accredited, 11 journals have not been consistent in publishing and there has been an increase in the number of articles published.   Abstrak Tahun 2020 terjadi proses migrasi penerbitan jurnal ilmiah berkala dari jurnal tercetak menjadi Open Journal System (OJS) pada jurnal-jurnal ilmiah yang dikelola lembaga pelatihan di bawah naungan Badan Litbang Kementerian Agama. Penelitian ini bertujuan untuk mengetahui kondisi terkini dari OJS dari segi aksesibilitas, konsistensi, akreditas, dan jumlah artikel yang diterbitkan pada tahun 2019 dan 2020. Pengumpulan data dilakukan melalui telaah dokumen yang dilakukan dengan mengakses dan memeriksa 17 situs alamat OJS lembaga pelatihan di bawah Badan Litbang Kementerian Agama. Hasil penelitian menjelaskan bahwa semua lembaga pelatihan memiliki alamat website jurnal ilmiah terbuka, dua jurnal tidak dapat diakses, 15 jurnal belum terakreditasi, 11 jurnal belum konsisten dalam penerbitan dan terjadi peningkatan jumlah artikel yang diterbitkan dari tahun 2019 ke tahun 2020.